Kinetics of the upper limb during table tennis topspin forehands in advanced and intermediate players - Iino, Y.; Kojima, T. (Sports Biomechanics, 2011)
The purpose of this study was to determine the significance of mechanical energy generation and transfer in the upper limb in generating the racket speed during table tennis topspin forehands. Nine advanced and eight intermediate table tennis players performed the forehand stroke at maximum effort against light and heavy backspin balls. Five high-speed video cameras operating at 200 fps were used to record the motions of the upper body of the players. The joint forces and torques of the racket arm were determined with inverse dynamics, and the amount of mechanical energy generated and transferred in the arm was determined. The shoulder internal rotation torque exerted by advanced players was significantly larger than that exerted by the intermediate players. Owing to a larger shoulder internal rotation torque, the advanced players transferred mechanical energy from the trunk of the body to the upper arm at a higher rate than the intermediate players could. Regression of the racket speed at ball impact on the energy transfer to the upper arm suggests that increase in the energy transfer may be an important factor for enabling intermediate players to generate a higher racket speed at impact in topspin forehands.